Implementasi Islam Nusantara dalam Tradisi Keagamaan di Lingkungan Sekolah - Aprianto Abdurahman; Dewi Nurhasanah; Pian Apianto; Rohayat Rohayat; Imam Asrofi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Islam Nusantara is a religious concept in Indonesia characterized by moderation, inclusiveness, adaptability to local culture, and emphasizing tolerance. The implementation of these values ​​in school religious practices has been inconsistent due to differing perspectives and rejection of local traditions. The purpose of this study is to describe the forms of school religious traditions, analyze the implementation of Islam Nusantara values ​​in these traditions, identify supporting and inhibiting factors, and explain their impact on student character. The research method used was a qualitative approach with a case study design. The research location was Qurrota A'yun Elementary School in Purwakarta. Data were collected through interviews, observation, and documentation. Based on the results of the study, the Principal and Islamic Religious Education Teachers understand the concept of Islam Nusantara as a harmonious integration of Islam with local culture within the corridors of faith and sharia. Its implementation is realized through structured religious traditions (the culture of greetings, dhuha prayer, murojaah, etc.) that successfully integrate local wisdom. A significant impact is an increase in politeness, tolerance, religiosity, and respect for local culture among students. Supporting factors include school leadership and teacher-parent collaboration, while differences in understanding become obstacles that are overcome through intensive communication. The implementation of Nusantara Islamic values ​​in school religious traditions has proven effective in shaping students' character to be moderate, tolerant, and respectful of tradition. Schools are advised to strengthen program planning with written guidelines and a measurable evaluation system to monitor character development on an ongoing basis.